2020
DOI: 10.3390/w12051429
|View full text |Cite
|
Sign up to set email alerts
|

Water Resources Management Strategies for Irrigated Agriculture in the Indus Basin of Pakistan

Abstract: Agriculture of Pakistan relies on the Indus basin, which is facing severe water scarcity conditions. Poor irrigation practices and lack of policy reforms are major threats for water and food security of the country. In this research, alternative water-saving strategies are evaluated through a high spatio-temporal water footprint (WF) assessment (1997–2016) for the Punjab and Sindh provinces, which cover an irrigated area of 17 million hectares in the Indus basin of Pakistan. The SPARE:WATER model is used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
(46 reference statements)
1
43
0
Order By: Relevance
“…Monitoring land use/land cover changes is fundamental for sustainable irrigation water management plans. The authors of [101,102] showed the importance of using the remote sensing techniques in order to detect LCLU changes and their impact on surface water in Nile Delta. Urban sprawl and rapid LCLU changes in the Nile Delta have a negative impact on water irrigation quality by increasing the concentration of contaminants [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring land use/land cover changes is fundamental for sustainable irrigation water management plans. The authors of [101,102] showed the importance of using the remote sensing techniques in order to detect LCLU changes and their impact on surface water in Nile Delta. Urban sprawl and rapid LCLU changes in the Nile Delta have a negative impact on water irrigation quality by increasing the concentration of contaminants [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, even in the water district with the biggest total water abstractions for irrigation (Thessaly), these abstractions represent about 50% of the theoretical annual available water resources [78]. Previous studies highlighted that optimising cropping patterns of the existing crops can result in an improvement of irrigation settings and in significant water savings [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrological modelling is a useful tool for the estimation of irrigation water needs at several scales [5,32,41]. As an example, spatial distributed hydrological modelling has supported the estimate of irrigation water needs at the country scale [5] as well as the estimation of the water footprint of crops to establish alternative management plans for more sustainable water use [9]. During the last decades, Remote Sensing (RS) has provided data with excessive spatial resolution, systematic revisit times and synoptic view of the Earth's surface [42].…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Amazonia, Brazil, green and blue WFs of agriculture (crop and pasture) in recent years (2000 and 2014) and future years (2030 and 2050) were modelled to study the impact of agricultural intensifications on crop water use [44]. In the Indus Basin, Pakistan, the WF of 17 million hectares of irrigated croplands in high spatiotemporal resolution was evaluated to support policymakers with a better vision of the national water and food security agenda [45]. In Punjab, Pakistan, blue, green, and grey WFs of cotton from production to textile were estimated to throw light on the WF of the textile industry [46].…”
Section: Introductionmentioning
confidence: 99%